Global research in arthroscopy of the anterior cruciate ligament: A bibliometric and visualized study - Visconti-Lopez, Fabriccio J. (2022)
Purpose: To carry out a bibliometric analysis of the scientific articles that address the topic of arthroscopy of the anterior cruciate ligament (ACL). Methods: A bibliographic search of the original articles published in orthopedics journals indexed in the Web of Science database until 2020 was carried out. Evaluation of compliance with the inclusion criteria was carried out in the Rayyan web application. The Bibliometrix package in the R programming language and VOSviewer were used to perform the bibliometric analysis. Results: 2249 articles published in 87 journals were included. The first publication on the subject was in 1980, and the highest number of publications was registered in 2020 (151) (annual percentage growth rate of 5.7). Fu FH was the author with the highest number of published articles, and the institutional affiliation with the highest number of original articles was the University of Pittsburgh. The most cited article was the study by Peterson et al. (2000) and the journal with the highest number of publications was Arthroscopy: the journal of arthroscopic and related surgery. United States had the highest frequency of publications and the highest number of total citations received by country. It was found on the network that the largest number of published studies had keywords such as: injuries and follow-up, whereas, in the most recent articles, the most common terms were risk-factors and outcomes. Conclusions: There is a sustained increase in scientific production on ACL arthroscopy among the world scientific community. Our results can be used for collaborative research purposes and by professionals seeking training in this topic.